the Pengaruh Pengaruh Faktor Gaya Hidup dan Status Sosial terhadap Perilaku Pembelian Sepatu Impor di Kota Banda Aceh: Faktor yang Mempengaruhi Perilaku Pembelian Sepatu Impor di Kota Banda Aceh - Mirza Murni; Cut Fitrika Syawalina; Said Firdaus (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2026)
The development of a modern-oriented lifestyle is very important for some people's lifestyles. Purchasing decisions for imported shoe products in Banda Aceh are still considered low because these products have relatively high prices so that only certain people can afford them. This study aims to examine the influence of lifestyle and social class on the buying behavior of imported shoes in Banda Aceh. The Research method using a quantitative approach.The data source for this study uses primary data. The sample in this study was the people of Banda Aceh who bought imported shoes, totaling 96 people. The data analysis technique used in this study is multiple linear regression. The results of the study indicate the influence of Lifestyle and Social Class simultaneously on the Purchase of Imported Shoe Products in the people of Banda Aceh.